Penggunaan Model Problem Based-Learning Terhadap Kemampuan Problem Solving pada Program Linear: Systematic Literature Review - Nadia, Nadia Putri Lestari (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
Problem solving is a crucial competency in mathematics learning. This study aims to determine, examine and conclude the impact of using the Problem Based Learning (PBL) model on students' mathematical problem solving on linear program material. The method used in this study is Systematic Literature Review (SLR) by tracing Sinta and Google Scholar indexed scientific articles published in the 2021-2025 range. The results of the analysis show that the PBL model consistently has a positive effect on improving students' problem solving. This finding has the potential to be a reference for improving more efficient mathematics learning strategies, especially in linear program material. keywords: problem solving; problem-based learning; program linear; Sytematic Literatur Review